Campur Kode Dan Alih Kode Tuturan Dalam Perdagangan Di Pasar Klewer Surakarta - Arif wijaya, Ginanjar; , Prof. Dr. H. Abdul Ngalim, MM.,M.Hum (2016)
Speech in commerce in market in Surakarta Klewer market often occurs code-mixing and code switching, code-mixing and a form of code contained in the trade speech in Surakarta Klewer market occur because of certain factors. This study has two objectives. (1) Mix the code and the code switching speech contained in Klewer market trading in Surakarta. (2) Factors that contributed to the code-mixing and code switching in speech Klewer market trading in Surakarta. This research uses descriptive qualitative method. A form of code-mixing in the speech of trade between sellers and buyers in the market there are five Klewer Surakarta. (1) Insertion ungsur-ungsur which are words. (2) Tangible group said. (3) Tangible clause. (4) Tangible repeated words. and (5) Tangible idiom / phrase. Judging from the two mixed classification code is code-mixing intern (into) and external (out). The realization of code switching in speech Klewer market trading in Surakarta there are two kinds of code rather discuss tangible and intangible rather than the code said. Rather tangible interpreter code four. (1) Transfer Indonesian code to the Java language. (2) Instead of Java language code into Indonesian. (3) Transfer Indonesian code into foreign languages. (4) Transfer of Foreign language code into Indonesian. Rather tangible code over said there were four. (1) Transfer of Indonesian in the Java language. (2) Transfer the Java language into the Indonesian language. (3) Transfer Indonesian into foreign languages. (4) Transfer to the Indonesian foreign language. Factors that contributed to the mixed code is contained in the trade speech in Surakarta Klewer market there are four. (1) Want to explain something / specific intent. (2) Since the situation. (3) Want to build intimacy between seller and buyer. (4) Due to satirize or praise. Factors that led to the emergence of code in the speech market trading surakarta Klewwer five. (1) Speaker / speaker. (2) The Listener (opponents said / hearer). (3) Changes in the situation because of the presence of a third person. (4) The subject. (5) Increase the sense of humor. Keywords: code-mixing and code switching in speech Klewer market trading in Surakarta